A REVIEW OF GRAFFITI AS VISUAL COMMUNICATION FORM: BIBLIOMETRIC ANALYSIS AND VISUALIZATION - Kim Jinoh; Donna Carollina (AKSA: Jurnal Desain Komunikasi Visual, 2023)
Currently, the presence of graffiti has existed in every corner of urban space in Indonesia. Its presence makes it one of the popular arts that applies a variety of visual elements as a medium of visual communication. Graffiti research itself in Indonesia is still very minimal. Especially those that focus on mapping research trends with the topic of graffiti as a visual communication medium. Thus, this research was conducted to examine trends with graffiti as a visual communication form. The analysis method used in this study was bibliometric analysis. The data used in this study was based on the Scopus database. The results found there are the research trends tend to be dynamic from 2009 until 2022. Based on the visualization results, it was found that the topic of graffiti as a visual communication form formed a network that was divided into 5 clusters, namely Red, Green, Blue, Yellow, and Purple clusters. From this network, co-occurrence is found based on keywords, titles, and abstracts where the theme of discussion with the largest node is art. From the results of this visualization, it was found that the topic of graffiti as a visual communication form still has an opportunity to be discussed in others themes outside of existing items.